Efficiency of Charcoal Briquettes Produce from Waste Bamboo Sticks at Buffet Restaurants in Xaythany District, Vientiane Capital - Phuangkhansai, Sysombath; Phonepaseuth, Phongphayboun; Mangnomek, Vienglasy; Phearkeo, Oley; Junthavexaiy, Loun (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
Bamboo is impotent natural resource for Laos; they are used for producing furniture, handicrafts, household items, and chopsticks, etc. Besides that, bamboo sticks are usually single-use in buffet restaurants nowadays, which generate waste afterward. From our survey indicate that 1,514g - 1,643g of bamboo sticks were generated per buffet restaurant in each day. This research aims to utilize of that waste as charcoal briquettes. Six ratios of briquettes were compared; three ratios of bamboo stick charcoal: cassava starch binder (w/w) include 1,000:50 (C1), 1,000:100 (C2), 1,000:150 (C3), and another three ratios of bamboo sticks charcoal (50%) mixed with (50%) white charcoal powder: cassava starch binder Vis. 500:500:50 (C4), 500:500:100 (C5), and 500:500:150 (C6) were compared with white charcoal as control (C0). Five hundred grams of each ratio was used in water boiling test experiments. Boiling time, total burning time and ash residual were determined. From the result, 49.04% of charcoal was obtained from bamboo stick carbonization. All ratios have a uniform without cracked, except (C1). The comparison results showed that the ratio of (C5) was found to be the best ratio with rapid burn, long burning duration, less ash residual compare with others ratios. This could be circular economy practise for those restaurant which has returned the waste utilized as fuel consumtion. Thus, this research leave the conclusion that bamboo stick charcoal briquette has a potential to be an alternative source of natural wood fuel for consumption in the future.